Three new species of Leptohyphes Eaton (Ephemeroptera: Leptohyphidae) from Colombia - Molineri, Carlos (2016)
Three new species of Leptohyphes Eaton,1882 (Ephemerotera: Leptohyphidae) are described,diagnosed and illustrated from nymphs collected in Colombia. Geographical ranges and ecological notes relating important environmental variables are given for each species. Leptohyphes andina sp. nov. is characterized by: forefemur length / maximum width 1.8-1.9,fore and hind margin of middle and hind femora with strong spine-like setae on elevated sockets,femoral surface covered by small pale spots,apex of femora with anterior margin roundly projected distally,tarsal claw only with 3-4 marginal denticles,pronotum with triangular lateral projection,hind wing pads present in female,gill formula 3/5/5/5/2,gill V with ventral extension on dorsal lamella. Leptohyphes quimbaya sp. nov. presents the following characters: body covered by hair-like setae,with paired short and blunt tubercles on abdominal terga V-IX,femora wide (forefemur length/ maximum width 1.6),fore and hind margin of femora with tiny spine-like setae,tarsal claws with 2-3 marginal denticles,pronotum with triangular (but apically blunt) lateral projection,hind wing pads present in females,gill formula 3/7/7/5/2,gill V without ventral extension on dorsal lamella. Leptohyphes calarca sp. nov. is distinguished by: pilose body,slender femora (forefemur length / maximum width 2.3),foremargin of middle and hind femora without setae,tarsal claws with 5 marginal denticles and 1 submarginal subapical denticle,pronotum strongly projected laterally,fore wingbuds blackish,hind wing pads present in females,gill formula 3/4/4/3/1,gill V with ventral extension on dorsal lamella.